2005
DOI: 10.1063/1.1888368
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of acetic acid on ice: Experiments and molecular dynamics simulations

Abstract: Adsorption study of acetic acid on ice surfaces was performed by combining experimental and theoretical approaches. The experiments were conducted between 193 and 223 K using a coated wall flow tube coupled to a mass spectrometric detection. Under our experimental conditions, acetic acid was mainly dimerized in the gas phase. The surface coverage increases with decreasing temperature and with increasing concentrations of acetic acid dimers. The obtained experimental surface coverages were fitted according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(102 citation statements)
references
References 19 publications
7
93
2
Order By: Relevance
“…The interaction with the ice surface could be strong enough to break the dimer form of AA; in other words, water ice can split the AA dimers. 14 Allouche and Bahr proposed the formation of stable dimers with one water molecule. 39 H 2 O molecules become attached to the pre-existing AA dimers by hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The interaction with the ice surface could be strong enough to break the dimer form of AA; in other words, water ice can split the AA dimers. 14 Allouche and Bahr proposed the formation of stable dimers with one water molecule. 39 H 2 O molecules become attached to the pre-existing AA dimers by hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…13 It is proposed that the adsorption of isolated AA dimers on ice is able to break the dimeric structure, but a near monolayer coverage of this dimer species can reform to oligomeric structures. 14 Classical molecular dynamic simulations demonstrated that AA is strongly trapped on the ice surface at 250 K. 15 Results show that partial solvation takes place, as in the case of FA, during acid adsorption at this temperature. The adsorption and incorporation processes of AA and FA are highly influenced by the formation of two hydrogen bonds between the carboxyl moiety and two water molecules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of simulation studies have thus been devoted to the characterization of the interactions between water molecules and aerosols but only a few of them have been specifically devoted to organic aerosols or organic surfaces. [2, 9-25] In contrast, such approaches have been widely used for ten years to describe the interactions between organic compounds and ice surfaces in the atmosphere, either based on ab initio calculations [26][27][28][29] or on classical simulations (Monte Carlo and molecular dynamics), [30][31][32][33][34][35][36][37][38][39][40][41][42][43] and it has been shown that these simulations led to a rather satisfactory agreement with experimental data [32-34, 38-41, 43] or in situ observations. [36] 3 While most of these studies focused on quite simple organic molecules, we recently used molecular dynamics simulations to characterize the details of the interaction between ice surfaces and more complex, difunctionalized molecules, such as hydroxyacetone [40] and oxalic acid.…”
Section: Introductionmentioning
confidence: 99%